A Mitochondrial Target Sequence Polymorphism in MnSOD Predicts Inferior Survival in Breast Cancer Patients Treated with Cyclophosphamide - Glynn, Sharon A. (2009)
PURPOSE: Manganese superoxide dismutase (MnSOD) protects against oxidative damage and modulates the efficacy of chemotherapeutic drugs. A functional single nucleotide polymorphism (SNP) in codon 16 of SOD2 (rs4880), which encodes MnSOD, results in a substitution of valine by alanine (Val16Ala). We hypothesized that this SNP affects breast cancer survival of patients receiving chemotherapy. EXPERIMENTAL DESIGN: Two patient populations from the United States (n=248) and Norway (n=340) were genotyped for Val16Ala. Kaplan-Meier survival and Cox Proportional-Hazards regression analyses were used to examine the relationship between Val16Ala and disease-specific survival. RESULTS: Val16Ala was significantly associated with breast cancer outcome in both patient populations. Carriers of the Ala allele had inferior survival rates in the multivariate analysis [Hazard ratio (HR) = 2.44; 95% confidence interval (CI), 1.11–5.37 in United States cohort and 1.91; 95% CI, 1.06–3.45 in Norway cohort for Ala/Ala versus Val/Val]. In an analysis of the combined cohorts, this association was significant for patients receiving adjuvant therapy (HR = 2.47; 95% CI, 1.46–4.19), but not for patients without it (HR = 1.47; 95% CI, 0.57–3.74). After further stratification by type of chemotherapy, the effect of the Ala allele was mostly restricted to cyclophosphamide-containing chemotherapy regimens (HR = 22.0; 95% CI, 5.22–92.9; Ala/Ala versus Val/Val). CONCLUSION: The Val16Ala polymorphism affects survival of patients receiving cyclophosphamide-containing chemotherapy. The findings provide the first evidence pointing toward a mechanism for cyclophosphamide-resistance in breast cancer patients.